Cybaeus (Araneae: Cybaeidae): the adenes species group of the Californian clade - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2019)
Species of North American Cybaeus L. Koch (Araneae: Dictynoidea: Cybaeidae) are common moist-forest spiders classified in Holarctic and Californian clades. Here we review the adenes species group of the Californian clade. We recognize nine species: Cybaeus adenes Chamberlin & Ivie, C. amicus Chamberlin & Ivie, C. auburn Bennett spec. nov., C. grizzlyi Schenkel, C. pearcei Bennett spec. nov., C. reducens Chamberlin & Ivie, C. sanbruno Bennett, C. schusteri Bennett spec. nov., and C. torosus Bennett spec. nov. The species of the adenes group have extremely restricted ranges in west central California from Sonoma and Napa Counties south to northern Monterey County and in east central California from Placer and El Dorado Counties. Descriptions, illustrations, range maps, and an identification key are provided for all species.